Is Bilateral Pulmonary Lobectomy Feasible in Patients with Bilateral Lung Cancers? - Hattori, Aritoshi; Suzuki, Kenji; Takamochi, Kazuya; Oh, Shiaki (The Thoracic and Cardiovascular Surgeon, 2015)
Background While aggressive surgical resection is an acceptable strategy for bilateral lung cancers, there are still some controversies regarding the appropriate indications of bilateral pulmonary lobectomy.Methods Between 1996 and 2012, 21 patients underwent bilateral pulmonary lobectomy for bilateral lung cancers. Postoperative complications after bilateral pulmonary lobectomy were defined based on the Common Terminology Criteria for Adverse Event Version 4.0 (National Cancer Institute, USA).Results In this study, 21 patients underwent bilateral pulmonary lobectomy by staged surgery for bilateral lung cancers. Thirteen patients (62%) recovered without any complications after the second surgery. Among the eight (38%) patients with postoperative complications, four had relatively minor complications of grade 1 or 2. In contrast, postoperative complications were frequently observed in patients who underwent right lower lobectomy, were age ≥ 70 years, or had larger tumor size (p = 0.0041, 0.0195, 0.0324). The mean hospital stay after the second surgery was 8.0 days. In-hospital mortality was found in five patients including three of respiratory failure. The median follow-up period for all patients was 40 months. The 5-year survival rate after bilateral pulmonary lobectomy was 61.7%.Conclusion Although appropriate patient selection and careful perioperative management are mandatory, bilateral pulmonary lobectomy could be an acceptable procedure for patients with bilateral lung cancers.
Keywords: bilateral pulmonary lobectomy; lung cancers; postoperative complication; survival